ANALISIS PERBANDINGAN DAYA HAMBAT EKSTRAK PIROLISIS DAN EKSTRAK MASERASI DAUN TEMBAKAU (Nicotiana tabacum L.) VAR VIRGINIA TERHADAP Fusarium oxysporum SECARA IN VITRO - Amelia Salsabila, (2023)
Fusarium oxysporum including non-dermatophyte fungus that causes onycomycosis. Cases of this fungal infection are susceptible to developing resistance, because this fungus can be refractory to commonly used antifungal drugs, so it's necessary to look for antifungal alternatives by using herbs, for example tobacco which was used as medicine in the 16th century. Tobacco leaves extract is known to inhibit the growth of fungi. This study aims to determine the comparison of inhibition between pyrolysis extract and maceration extract of tobacco leaves (Nicotiana tabacum L.) Virginia variant on fungal growth Fusarium oxysporum in vitro. The samples for this experimental study were pyrolysis extract and tobacco leaves maceration with various concentrations (100%, 80%, 60%, 40%, and 20%) and used the well-diffusion antifungal test method and observed whether an inhibition zone was formed around the wells. Analysis of the Post Hoc Mann Whitney test with a significance of p<0.05 indicating a significant difference in each concentration and test independent sample T-test with a p value <0.05 there was a significant difference in the two extractions. The largest inhibition zone was in the pyrolysis extract with an average of 45.06 mm while in the maceration extract it was 22.46 mm.